A note on gray whale distribution and abundance in the Magdalena Bay Complex, México during the 1997 winter season - Perez-Cortez M. , Hector; Urban R. , Jorge; Loreto C. , Pablo A. (J. Cetacean Res. Manage., 2023)
The goal of this study was to determine the distribution and abundance of gray whales, distinguishing between cow-calf pairs and single whales, in the different areas forming the Magdalena Bay Complex at Baja California Sur, Mexico. The lagoon complex comprises three well-defined zones: Santo Domingo Channel or Puerto Adolfo López Mateos region in the north; the central part properly known as Magdalena Bay; and the southern portion, Almejas Bay. The study period spanned eight weeks during the 1997 winter season. Fifteen surveys were conducted: 5 at Santo Domingo Channel, 7 at Magdalena Bay and 3 at Almejas Bay. Maximum combined counts by area and date were as follows: Santo Domingo Channel: 100 whales (83 cow-calf pairs and 17 single whales) on 27 February; Magdalena Bay: 81 whales (9 cow-calf pairs and 72 singles) on 14 February; and Almejas Bay: 109 whales (15 cow-calf pairs and 94 single whales) on 28 February. Santo Domingo Channel was the main calving zone within the lagoon complex and had the highest number of cow-calf pairs; for every count in this zone the number of cow-calf pairs was always higher than that of single whales. In contrast, Magdalena and Almejas Bays were mainly used for courtship and mating, or aggregation areas for young and immature whales. It is recommended that these studies continue and attempt to cover the entire season, and complete even coverage of all areas within the Complex. This will allow more effective management and regulation of human activities affecting gray whales within the Magdalena Bay lagoon complex.